A caspase cleavage fragment of p115 induces fragmentation of the Golgi apparatus and apoptosis - Chiu, Raymond (The Rockefeller University Press, 2002)
In mammalian cells, the Golgi apparatus undergoes extensive fragmentation during apoptosis. p115 is a key vesicle tethering protein required for maintaining the structural organization of the Golgi apparatus. Here, we demonstrate that p115 was cleaved during apoptosis by caspases 3 and 8. Compared with control cells expressing native p115, those expressing a cleavage-resistant form of p115 delayed Golgi fragmentation during apoptosis. Expression of cDNAs encoding full-length or an NH(2)-terminal caspase cleavage fragment of p115 had no effect on Golgi morphology. In contrast, expression of the COOH-terminal caspase cleavage product of p115 itself caused Golgi fragmentation. Furthermore, this fragment translocated to the nucleus and its expression was sufficient to induce apoptosis. Most significantly, in vivo expression of the COOH-terminal fragment in the presence of caspase inhibitors, or upon coexpression with a cleavage-resistant mutant of p115, showed that p115 degradation plays a key role in amplifying the apoptotic response independently of Golgi fragmentation.